Estimate of Propriety of Business Cycle Forecasts of Enterprises on Example of Retail Trade Units - Kowalewski, Grzegorz (Regional Barometer. Analyses & Prognoses, 2008)
Researching of quality of forecast formulated is purpose of article by directors of retail trade units in Poland. In weak situation of propriety of forecast try to find it reason. Two meters ex post employ for estimate of accuracy of forecast fast: Theil and for differences divergence. Article is based on empirical research. Results of business condition surveys are base of estimate of forecast.